2018
DOI: 10.1037/rep0000187
|View full text |Cite
|
Sign up to set email alerts
|

Social Participation and Navigation (SPAN) program for adolescents with acquired brain injury: Pilot findings.

Abstract: Results support the feasibility of the program, because participants were able to successfully meet with their coaches and use the app to develop and accomplish social participation goals. Further research will be needed to refine the app and program, particularly when reaching out to populations beyond traumatic brain injury. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(55 citation statements)
references
References 56 publications
1
54
0
Order By: Relevance
“…In particular, 6 studies focused on the Counselor-Assisted Problem Solving (CAPS) intervention [53, 54, 56, 6971], 2 studies on the Online Family Problem-Solving (OFPS) program [55, 72], and 4 studies on the Teen Online Problem-Solving (TOPS) intervention [22, 23, 57, 58]. The remaining 2 studies focused on the Social Participation and Navigation (SPAN) intervention [48, 73], a training aimed at improving social abilities in children with TBI or brain tumor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, 6 studies focused on the Counselor-Assisted Problem Solving (CAPS) intervention [53, 54, 56, 6971], 2 studies on the Online Family Problem-Solving (OFPS) program [55, 72], and 4 studies on the Teen Online Problem-Solving (TOPS) intervention [22, 23, 57, 58]. The remaining 2 studies focused on the Social Participation and Navigation (SPAN) intervention [48, 73], a training aimed at improving social abilities in children with TBI or brain tumor.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, 4 records from software programs' website [4447] were found. One more article meeting the eligibility criteria was found from expert network [48], leading to a total of 32 studies considered for this work. Figure 1 depicts the study inclusion procedure.…”
Section: Methodsmentioning
confidence: 99%
“…Limited access to psychological services has fuelled increasing interest in implementing technology to broaden intervention options. Some studies involved telephone-based [1821] or computer-based [22, 23] interventions, while others employed diverse technologies such web-based programs [24, 25], mobile applications [26], videogames [27], and virtual reality [28].…”
Section: Resultsmentioning
confidence: 99%
“…More recently, peer support interventions have been used to support increased social participation and effective social goal setting using the Social Participation and Navigation (SPAN) program for adolescents with acquired brain injury. 91 In this program, adolescents are provided with online resources to support social participation and social goal setting. The adolescents also participate in Skype interactions with peer coaches who support the participants in identifying social goals, developing a plan of goaldirected behavior, and identifying and addressing barriers if goals were not achieved.…”
Section: Peer Involvementmentioning
confidence: 99%
“…Additionally, the adolescent participants reported greater confidence in their ability to participate socially and develop social participation goals and plans. 91 There is also literature to support the efficacy of arts-based interventions focusing on theater skills training to facilitate social skills and participation for youth with TBI. Two studies reported on an intervention during which participants met daily for 4 hours over a period of 3 weeks in a theater skills program that focused on enhancing five main abilities including (1) collaboration, (2) self-awareness/ awareness of others and the environment, (3) relaxation, (4) listening, and (5) curiosity and imagination.…”
Section: Peer Involvementmentioning
confidence: 99%